Sistema integrado de monitoramento, registro e gravação de chamadas para assinantes de telefonia fixa - Tolari, Eduardo (2011)
This text aims to present a simple and low cost solution for fixed line customers, so that they can independently manage the residential telephone traffic. It was developed a software for Microsoft Windows platform that using a dial-up modem, it has the ability to monitor the telephone line, recording all occurrences of calling. It also allows the creation, reception and call recording, digital audio playback during the calling, besides offering a phonebook. It is provided the option to generate a report containing all outgoing and incoming calls, recorded by the software. The correct operation of all functions of the project was checked through testing.